Application of Path Analysis in identification of dominant effective meteorological parameters on ET0 in West Azarbaijan - Yagob Dinpashoh; Masoumeh Foroughi (تحقیقات کاربردی علوم جغرافیایی)
Reference evapotranspiration (ET0) is a climatic parameter and can be computed from weather data. It is one of the most important hydrological parameters for calculating crop water demand, scheduling irrigation systems, preparing input data to hydrological water-balance models, regional water resources assessment, and planning and management for a region and/or a basin. The climatic data from synoptic stations with more than 20 years continues record in West Azarbaijan province was used. The well-known FAO-PM56 method was used to calculate the ET0. Then Multiple linear Regression (MLR) was used to estimate the ET0. The RMSE, MEA, NSH, and R2 were used to evaluate the performance of the MLR model. Then, the correlation coefficient (r) between ET0 and each of the meteorological parameters was obtained. And finally, with using Path analysis method, the influence of direct (P) and indirect effects of the meteorological parameters on ET0 was calculated. In the studied synoptic stations, NSH between 0.91 and 0.99,   R2 between 0.91 and 0.99, RMSE between 0.05 and 0.15, and MEA between 0.04 and 0.12 were obtained. Also, it was found that the wind speed at all of stations had a significant correlation (at the 0.01% level) with ET0. The path analysis results showed that the maximum value of P (direct effect of meteorological parameters on ET0) in all of the stations belongs to wind speed. The P value of wind speed in Urmia equal to 0.85, Piranshahr equal to 0.99, Takab equal to 0.97, Khoy equal to 0.90, Sardasht equal to 1.06, and Mahabad equal to 0.78 are obtained.